Glucose and Lipid Homeostasis and Inflammation in Humans Following an Isocaloric Ketogenic Diet. Issue 6 (8th May 2019) - Rosenbaum, Michael; Hall, Kevin D.; Guo, Juen; Ravussin, Eric; Mayer, Laurel S.; Reitman, Marc L.; Smith, Steven R.; Walsh, B. Timothy; Leibel, Rudolph L.
Abstract : Objective: The objective of this study was to measure changes in glucose, lipid, and inflammation parameters after transitioning from a baseline diet (BD) to an isocaloric ketogenic diet (KD). Methods: Glucose homeostasis, lipid homeostasis, and inflammation were studied in 17 men (BMI: 25‐35 kg/m 2 ) during 4 weeks of a BD (15% protein, 50% carbohydrate, 35% fat) followed by 4 weeks of an isocaloric KD (15% protein, 5% carbohydrate, 80% fat). Postprandial responses were assessed following mixed‐meal tests matched to compositions of the BD (control meal [CM]) and KD (ketogenic meal). Results: Fasting ketones, glycerol, free fatty acids, glucagon, adiponectin, gastric inhibitory peptide, total and low‐density lipoprotein cholesterol, and C‐reactive protein were significantly increased on the KD. Fasting insulin, C‐peptides, triglycerides, and fibroblast growth factor 21 were significantly decreased. During the KD, the glucose area under the curve was significantly higher with both test meals, and the insulin area under the curve was significantly higher only for the CM. Analyses of glucose homeostasis suggested that the KD insulin sensitivity decreased during the CM but increased during the ketogenic meal. Insulin‐mediated antilipolysis was decreased on the KD regardless of meal type. Conclusions: Switching to the KD was associated with increased cholesterol and inflammatory markers, decreased triglycerides, and decreased insulin‐mediated antilipolysis. Glucose homeostasis parameters were diet dependent and test meal dependent.